The Relationship Between Knowledge Of Mothers Aged 40 – 45 Years With Anxiety Facingmenopause In The Village Kung Pegasing Sub-District - Rahmayani, Rahmayani (Jurnal EduHealth, 2023)
Menopouse is the last menstruation, or the occurrence of the last menstruation, the diagnosis is made after there has been amenorrhea for at least one year. The cessation of menstruation can be preceded by a longer menstrual cycle with reduced bleeding. The age of menopouse is influenced by heredity, general health and life patterns, there is a tendency for menopause to occur at an older age. The population in this study was all mothers aged 40-45 years who were in Kung Village, Pegasing District, Central Aceh Regency, as many as 35 respondents who were determined using total sampling, which is sampling based on the entire total population. The study was conducted from 15 to 22 September 2023 using questionnaires. The results of this study showed that there was a significant relationship between the knowledge of mothers aged 40-45 years with anxiety facing menopause P Value 0.009 (P ≤ 0.05)